The Role of Woman in Black Beauty by Anna Sewell through Representation - Pariama, Stevane Delsancy; Sriastuti, Anna (Proceedings of English Linguistics and Literature, 2024)
Women often face stereotypes of being nurturing or empathetic due to their historical roles as caregivers, leading to unfair judgments based on emotions compared to men's rationality. Because of this situation Simone de Beauvoir, a French philosopher, later criticized gender inequality in her writing "The Second Sex”. This paper delves into the phenomenon of slavery endured by women and children during the Victorian era, as depicted in Anna Sewell`s "Black Beauty". By contextualizing the characters' experiences within historical realities, this study contributes to a broader comprehension of the representation of gender oppression and woman slavery in that book. Using Stuart Hall's representation theory, it analyzes how societal norms and power dynamics during Queen Victoria's reign shape the portrayal of female characters. Hall's theory highlights that representations are constructed through cultural and historical contexts, not direct reflections of reality. Ultimately, the analysis shows that "Black Beauty" effectively portrays the harsh realities of slavery, especially for women and children, making it a significant social critique of its time.